Belajar Toleransi dari Masyarakat Desa Klinting Kecamatan Somagede Kabupaten Banyumas - Rakhmat Agung Pramadani; Tania Ridi Putri Mentari; Hilmi Al Hazmi Hidaya; Zahira Fina Indraini; Tri Rini Widyastuti (Universitas Lambung Mangkurat, 2025)
Tolerance and harmony between religious communities in Klinting Village are the main points discussed in this article. Klinting Village is an example of how tolerance between religious communities should be implemented. In the midst of the decreasing level of tolerance in Indonesia as a multicultural country, social harmony in Klinting Village can be an example of multicultural society to avoid unwanted disputes in the future due to differences. The research method used is a qualitative method with a case study approach. Data collection techniques use in-depth interviews, observation and documentation. The technique for determining informants used purposive sampling with a total of six informants. The results of the research show that tolerance between followers of Islam and Hinduism and other religions in Klinting Village is still going well, giving rise to harmony between community members. All elements of society play an important role in maintaining the values of tolerance in Klinting Village so that conflicts do not easily occur which can later develop into prolonged conflicts. All religious communities, both Muslims and Hindus and other religions, continue to maintain tolerance and peace between each other so that social harmony in Klinting Village is maintained to this day